Early Detection of Indonesia’s Vulnerability to Currency Crisis - Oyong, Rosa Agustina; Didong, Rustam; Safuan, Sugiharso; Warjiyo, Perry (International Journal of Economics and Financial Issues, 2018)
This study addresses an Early Warning System (EWS) of currency crisis, as well as proposes EWS with an approach of early detection of vulnerability to crisis. Detecting vulnerabilities is a more effective step because it gives the policymakers plenty of time before determining the right policy responses to anticipate and prevent a crisis. The data used are monthly macroeconomic data from January 2002 to December 2012. The steps taken were to identify currency crises, determine indicators of currency crises, determine vulnerability indicators to currency crises with logistic regression, and build vulnerability index to currency crises with fuzzy logic. This research builds vulnerability index to currency crisis with vulnerability level consisting of normal, alert, standby, and crisis suspected condition. This research provides EWS with the approach of early detection of vulnerability to currency crisis and builds vulnerability index that can be used in assessing and monitoring economic condition. Keywords: Currency Crisis, Early Warning System, Vulnerability JEL Classifications: G01, C49